DESIGN AND IMPLEMENTATION OF PHOTOVOLTAIC-WATER PUMPING SYSTEM FOR USE IN IRAQ - Hameed Habeeb, Waleed (Journal of Engineering and Sustainable Development, 2018)
In this research, a well water pumping system utilizing solar cells generated electric power is designed and implemented. We assumed a village located in a remote area of southern Baghdad for providing a quantity of water of 30000lit/day (30m3/day) to meet the daily needs of the quench and irrigation. Calculations show that the amount of water required can be obtained from a well of water head (15m) by using an array of solar cells that gives a power of (1300W) to submersible pumps capable of raising water by converting electrical energy to dynamic power. The cost of the pumping system using solar energy is more economical and less expensive than using a diesel pumping system. It is recommended to use the present solar energy pumping system in Iraq as it is one of the richest countries with solar power; however, suffers nowadays a scarcity of surface water.